Ne/kritická reflexe minulosti a přeshraniční spolupráce v trojmezních Euroregionech Nisa a Šumava. Na cestě od nostalgického hledání kořenů k dialogickému vzpomínání? - Kamil Fleissner; Karel B. Müller; Daniel Kný; Luděk Fráně (Historicka Sociologie, 2022)
The research article aims to contribute to the discussion on the process of Europeanization of collective memory. We examine the relationship between non/reflexive memory approaches and cross-border cooperation (CBC) in the triangle Euroregions Nisa and Šumava. We assume that key local agents of CBC defend dialogic remembering approach, therefore contribute to the process of horizontal Europeanization. To test this assumption, we conducted a questionnaire survey with 79 mayors and 52 semi-structured interviews with various agents in CBC in all sides of both Euroregions. Collected statistic data were analysed through the use of crosstabulation. In the interviews were identified multiple discourses on the historical conflicts and CBC. We interpreted both quantitative and qualitative data using the concept of the active border [Müller 2014, 2018] and four models of dealing with the traumatic past [Assman 2010]. We found evidence that traumatic past ceases to be perceived as a barrier and becomes to be seen as a catalyst for CBC. In this process, the following factors were identified as most crucial: structural perception of memory, cross-border socialisation, attachment towards EU project and, above all, generational gap. We prove that the leading supporters of dialogic remembering are representatives of the middle-aged generation of mayors, for whom the re/construction of cross-border relationships have become a lifelong challenge.